Hello Bundle / Ili Farhana Hasdi ... [et al.] - Hasdi, Ili Farhana; Norisham, Nur Syamimi; Mat Zul, Ain Alia Arissa; Azhar, Fatin Azhan; Abdul Razak, Nurul Muyassarah; Muhammad Al' Munawir, Nur Alia Nadia (2021)
The Business Model Canvas (BMC) has been useful for mentoring in the design of new products and services through its nine basic elements in terms of logical and emotional perspectives. This can also provide understanding to our group to share perspectives, ideas, and thoughts about the product, and ensure a clear understanding between staff and make good and strategic performance measures in design. This BMC can also help each company in understanding their business model, competitors, and customers well. The BMC is very important for us to start our business, which is Hello Bundle. This is because BMC will help our business to achieve its goals and objectives. In addition, Hello Bundle will teach many of our competitors by mapping and documenting our business models. By using this material, we will get a more in-depth picture of what consumers want and what we want to pay for. However, our business has a better picture of how customer desires need to be met in the industry and not just in our place. Hello Bundle, is located in the middle of Klang Valley and runs by 6 employees namely Ili Farhana, Nur Syamimi, Ain Alia Arissa, Fatin Azhan, Nurul Muyassarah, and Nur Alia Nadia. We have experience working in a bundle store, therefore, we set up the Hello Bundle business. Our business only focuses on things like beautiful clothes, fabrics that are very comfortable and undamaged for our customers. This Hello Bundle business is different from other businesses. This is because we provide clothes whose fabrics are very different. Lastly, for this business to succeed, we need to have successful relationships with our customers, because to keep them loyal to the business we run and establish trust with them without any problems.